2010
DOI: 10.1093/eurheartj/ehq326
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated and under-recognized: the late consequences of acute coronary syndrome (GRACE UK-Belgian Study)

Abstract: The GRACE risk score predicts early and 5 year death and CVD/MI. Five year morbidity and mortality are as high in patients following non-ST MI and UA as seen following STEMI. Their morbidity burden is high (MI, stroke, readmissions) and the substantial late mortality in non-STE ACS is under-recognized. The findings highlight the importance of pursuing novel approaches to diminish long-term risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
248
0
24

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(284 citation statements)
references
References 22 publications
3
248
0
24
Order By: Relevance
“…These results are comparable to the Filipiak et al (2014) study, performed with a group of 906 patients suffering from ACS and with an average age of 63 years, where the death rate was 29%, as well as with another study, conducted by Ezekowitz et al (2009), with a population-based cohort of 7,733 patients above 65 years, where the death rate was 28%. The multicentre research GRACE performed on 3,721 patients in Great Britain (2065 patients) and Belgium (1656 patients) showed that 20.0% of deaths had followed myocardial infarction, which was comparable with the result obtained in our research during a 5-year follow-up, including cases with STEMI -19.0%, NSTEMI -22.0%, and unstable angina -18.0% (Fox et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…These results are comparable to the Filipiak et al (2014) study, performed with a group of 906 patients suffering from ACS and with an average age of 63 years, where the death rate was 29%, as well as with another study, conducted by Ezekowitz et al (2009), with a population-based cohort of 7,733 patients above 65 years, where the death rate was 28%. The multicentre research GRACE performed on 3,721 patients in Great Britain (2065 patients) and Belgium (1656 patients) showed that 20.0% of deaths had followed myocardial infarction, which was comparable with the result obtained in our research during a 5-year follow-up, including cases with STEMI -19.0%, NSTEMI -22.0%, and unstable angina -18.0% (Fox et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The aim in this study was to assess the clinical evolution of 234 hospitalized patients due to the The participants' characteristics regarding the predominance of male and elderly patients is similar to other studies of cardiac patients (8)(9)(10) . These variables are strongly associated with coronary patients' clinical evolution and mortality due to ACS.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, patients with a substantial risk of recurrent events have an important unmet need for better secondary prevention. 28 A combination of antiplatelet and anticoagulant agents seems to be an attractive approach. However, such broad antithrombotic therapy may also pose an unacceptable risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%